A NITIDULID PARASITOID, Zeteticontus insularis (HOWARD (HYMENOPTERA: ENCYRTIDAE) PRESENT IN SÃO PAULO. WITH CLARAFICATION ON ITS HOST - Coler, Reginaldo R.; Williams, Roger N.; Berti Filho, Evôneo (REVISTA DE AGRICULTURA, 2015)
A NITIDULID PARASITOID, Zeteticontus insularis (HOWARD (HYMENOPTERA: ENCYRTIDAE) PRESENT IN SÃO PAULO. WITH CLARAFICATION ON ITS HOST